THE ROLE OF ENVIRONMENTAL KNOWLEDGE IN MEDIATING THE RELATIONSHIP BETWEEN GREEN PROMOTION AND GREEN PACKAGING ON GREEN PURCHASE BEHAVIOR IN EASY GREEN PRODUCTS BY UNILEVER - Zidan Basyarahil Rais Pambudi; Putu Nina Madiawati; Arry Widodo (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The increasing environmental issues, particularly the problem of plastic waste in Indonesia, as well as the gap between awareness and purchasing behavior of environmentally friendly products, have become important phenomena in this study. This study aims to analyze the effect of green promotion and green packaging on green purchase behavior, as well as to examine the role of environmental knowledge as a mediating variable in Easy Green Unilever products. In this study, data were collected through a survey distributed to users of Easy Green Unilever products in Indonesia, with a total of 400 respondents obtained. The research method employed a descriptive and quantitative approach, using non-probability sampling with a purposive sampling technique. In data processing, this study utilized SmartPLS software. The results indicate that green promotion and green packaging have a positive and significant effect on green purchase behavior. In addition, environmental knowledge is proven to have a significant effect on green purchase behavior and is able to mediate the relationship between green promotion and green packaging on green purchase behavior. The conclusion of this study emphasizes that increasing consumers’ environmental knowledge is a key factor in strengthening the effectiveness of green marketing strategies in encouraging environmentally friendly purchasing behavior.